Electoral reforms in India: A Critical study - RAJENDRAN, KUMAR; RAJENDRAN, KUMAR; KUMAR, S. K. ASOK (International Journal of Psychosocial Rehabilitation, 2020)
India is the largest democracy in the world, but due tocertain reasons, democracy is not working properly. Political analysts say there are some undermining reasons for this failure. The present study aims to explain the major electoral reforms in India. These reforms were powerful enough that they made remarkable changes in the election system in India. The study also ventures into the nuances behind each electoral reforms and the way in which it revitalized the total electoral system in India.